The combined effect of accounting measurement and disclosure on investment decision-making in Iraqi commercial banks (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The current research aims to demonstrate the combined impact of measurement and accounting disclosure on investment decisions in Iraqi commercial banks. To achieve the objective of this research, a questionnaire was designed and distributed to a group of bank employees to clarify the awareness of employees about the importance and impact of measurement and accounting disclosure on investment decisions .)250) questionnaires were distributed, (188) of which are valid for analysis. In light of this, the research came up with a set of results, most notably that the combined effect of measurement and accounting disclosure contributes to improving the quality of investment decision-making in Iraqi commercial banks، Based on the conclusions reached, the study recommends that Iraqi commercial banks should pay great attention to improving the ability of their employees with regard to measurement and accounting disclosure to improve banking performance through holding seminars to stimulate intellectual energies and develop the ability to make investment decisions.